2002
DOI: 10.1080/08964280209596396
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Sleep Hygiene Awareness, Sleep Hygiene Practices, and Sleep Quality in University Students

Abstract: College students are known for their variable sleep schedules. Such schedules, along with other common student practices (e.g., alcohol and caffeine consumption), are associated with poor sleep hygiene. Researchers have demonstrated in clinical populations that improving sleep hygiene knowledge and practices is an effective treatment for insomnia. However, researchers who have examined relationships between sleep hygiene and practices in nonclinical samples and overall sleep quality have produced inconsistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
273
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(321 citation statements)
references
References 35 publications
29
273
1
7
Order By: Relevance
“…It is known that university students have a different sleep rythm. These rythms lead to common student habits (consumption of alcohol and caffeine, environmental noise, go into sleep in a sad mode) associated with poor sleep hygiene and quality (Brown et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that university students have a different sleep rythm. These rythms lead to common student habits (consumption of alcohol and caffeine, environmental noise, go into sleep in a sad mode) associated with poor sleep hygiene and quality (Brown et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Students should understand the effects of caffeine, alcohol, napping, varied sleep schedules, and exercise on sleep problems . Evidence demonstrates that in a population without sleep disturbances, this strategy increases knowledge of sleep hygiene which results in better sleep practices and consequently better sleep quality (Brown, Buboltz, & Soper, 2006;Brown, Buboltz, & Soper, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep hygiene is a term used to describe a collection of behaviours related to the promotion of good sleep [18]. It is usually recommended that good habits and behaviours can enhance sleep quality and quantity.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that sleep hygiene practice was significantly associated with sleep quality. Poor sleep hygiene practices led to a higher prevalence of insomnia and sleeping problems [18]. Based on the National Sleep Foundation [20], sleep hygiene promoted healthy sleep and daytime alertness.…”
Section: Introductionmentioning
confidence: 99%